2014
DOI: 10.1007/s00259-014-2706-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing bone marrow involvement in Hodgkin’s lymphoma by FDG-PET/CT

Abstract: FDG-PET/CT demonstrated BMI in 15% of patients with newly diagnosed HL. Diagnosis of BMI in HL by FDG-PET/CT was more sensitive than iBMB with potential upstage in 11% of patients. The most common pattern of FDG-PET/CT BMI was multifocal (at least three foci) skeletal FDG uptake, with at least one focus in the pelvis or vertebrae and no corresponding CT lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…This discrepancy is probably accounted by the thorough imaging review in our study, whereas in other studies data were based on nuclear medicine reports only. Consistent with previous literature (9,12,14,23), the results of this study confirm a clear correlation between strong diffuse BM uptake and some clinical parameters, such as lower hemoglobin level and higher leukocyte count. In this patient group, we also frequently noticed a strong diffuse uptake in the spleen, younger age, bulky disease, and lower levels of albumin compared with patients with no 18 F-FDG uptake in BM.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This discrepancy is probably accounted by the thorough imaging review in our study, whereas in other studies data were based on nuclear medicine reports only. Consistent with previous literature (9,12,14,23), the results of this study confirm a clear correlation between strong diffuse BM uptake and some clinical parameters, such as lower hemoglobin level and higher leukocyte count. In this patient group, we also frequently noticed a strong diffuse uptake in the spleen, younger age, bulky disease, and lower levels of albumin compared with patients with no 18 F-FDG uptake in BM.…”
Section: Discussionsupporting
confidence: 93%
“…In the present analysis of 180 patients with treatment-naïve HL, we first gave a detailed description of BM 18 F-FDG uptake patterns to provide helpful key points for BMI assessment in PET/CT-staged patients. The significance of pure strong diffuse BM uptake is still unknown, but probably not related to BMI by neoplastic tissue, as recently stressed (8,12). Moreover, we confirmed that BMB is not a clinically relevant diagnostic tool, because of its scarce sensitivity and low likelihood to upstage PET/CT-staged patients (no patient upstaged from limited to advanced stage by BMB), thus far confirming that in the PET era BMB can be safely omitted for HL staging (8,19,20).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…27 51 FDG-PET/CT and BMB have a high concordance rate (w80%) for detecting bone marrow involvement. [48][49][50]52,53 In discordant cases of a positive PET scan and negative BMB, the most common causes are sampling error and diffuse uptake due to reactive marrow (Fig. 4).…”
Section: Assessment Of Bone Marrow Involvement At Initial Stagingmentioning
confidence: 99%